Rhodococcus equi Joint Sepsis and Osteomyelitis Is Associated With a Grave Prognosis in Foals - Ruocco, Nicholas A.; Luedke, Lauren K.; Fortier, Lisa A.; Ducharme, Norm G.; Reesink, Heidi L. (Frontiers in Veterinary Science, 2020)
The most common pathologic manifestation of R. equi, a gram-positive, facultative intracellular bacterium, is pyogranulomatous pneumonia in foals and weanlings. Hematogenous spread of bacteria may subsequently occur, resulting in joint sepsis, osteomyelitis or subcutaneous abscessation. Medical records from horses presenting to the Cornell University Equine Hospital from 1998-2018 were reviewed for cases diagnosed with R. equi joint and/or bone infection, and information about case progression and outcome were analyzed. We hypothesized that, despite advances in diagnostic imaging, antimicrobials and antimicrobial delivery methods, the prognosis for R. equi joint sepsis and osteomyelitis remains grave for athletic activity and poor for survival. The twelve cases that met the review criteria had a mortality rate of 84% (10/12), with one case lost to follow up after discharge and one case discharged with a grave prognosis for athleticism.